Development clusters for Small Places and Territorial Cohesion Cities for a more balanced and cohesive Europe? - Medeiros, E. (European rural policy at a crossroads? Rethinking needs, objectives, and measures, 2022)
• To achieve territorial cohesion in a given territory there is a need that socioeconomic lagging regions perform better than leading regions in most territorial development indicators over a period of time. Here, it is widely known that rural areas are often associated with comparable under-performing development trends. • So how what does regional development theory proposes to correct this mainstream scenario? • If one looks at the evolution of mainstream regional development paradigms, one can notice the increasing consideration of encompassing endogenous economic factors in regional development strategies; • More recent regional development theories highlight the need to consider key regional institutions, players and agencies to foster regional development; • Instead, I propose a more comprehensive approach for regional development which integrates six existing development paradigms, including the goal for a more balanced and cohesive territory. • Indeed, this has been an EU policy goal for several decades. However, all existing studies which have measured territorial cohesion trends, including Iberian and Scandinavian peninsulas, have showed that despite the positive impacts of EU Cohesion Policy in promoting regional development trends in almost all EU territories, it has not contributed to achieve territorial cohesion trends at the national level. In this context, I recently proposed an alternative policy paradigm to effectively achieve this policy goal names: Territorial Cohesion Cities, which basically proposes that the bulk of EU Cohesion Funding is concentrated in medium cities located in lagging regions. • So how can we deal with rural areas which normally do not have large or medium urban areas acting as drivers of regional development? • Well, based on recent research presented by Beer & Clower ‘cluster development’ is identified as one of the key ingredients for regional development. It is however, widely known that despite the advantages of regional clustering there are a few disadvantages such as the excessive dependency on a single economic domain; • In this context, we propose that the bulk of the public funding destined to develop rural areas should target municipality clusters collective strategies rather than individual municipal strategies. This is called the ‘Development Clusters for Small Places‘ theory, supported by the possibility of intermunicipal collaboration in four main domains: (i) the exploration of functional linkages and interdependences; (ii) acessibility and conectivity related advantages; (iii) Economic Circularity and Specialisation, and (iv) Territorial Cooperation and Governance potential advantages in small places • But what is a small place? – This depends from country to country, but normally encompasses a territory with small/medium urban settlements in a national context surrounded by rural areas. • Norway is an eloquent example of a country with vast rural areas and small urban settlements • And if one takes one of its regions (Innlandet), it is possible to apply Development Clusters for Small Places theory by using like the ‘Local Labour Markets’ to identify functional areas within certain municipality clusters which share similar development challenges that would make a more efficient use of regional development funding; • Likewise, data on economic specialisation can unveil municipal clusters which could join efforts in maximizing their development strategies to compete in the global market in a given economic activity; • It is safe to say that when it comes to cross-border cooperation, municipal clustering is already been experimented long ago, especially in the Nordic regions and in particular in Innlandet (ARKO and TRUST); • Finally, if one considers existing connectivity and accessibility connections in Innlandet, it is also possible to identify six distinct municipal clusters which could cooperation in several development domains with higher levels of effectiveness and efficiency; • In the end, we presented a theoretical rationale to develop Small Places by funding municipality clusters rather than individual municipalities since the latter approach has not revealed as the most effective way to spend EU development funding from the examples we know, and that would complement the policy rationale of the territorial cohesion cities as a concrete theoretical solution to achieving territorial cohesion.